ANTAGONIST, ANTIBACTERIAL ACTIVITY OF Stapylocossus aureus AND ISOLATE OF ORAL BACTERIA FROM THE ENDOGENOUS FUNGUS Apis dorsata BINGHAMI NEST - Dina Rombot; Ellen Adil; Mario Walean; Virjinia Bastian (Universitas Negeri Manado, 2021)
Apis dorsata Binghami is a honey bee endemic to Indonesia, living naturally in the forests of Sulawesi. This study aimed to obtain isolates and characteristics of endogenous fungi antibiotic activity from Apis dorsata Binghami nest. The study consisted of isolation of fungi from beehives using potato dextro agar, pure culture of fungi, antagonist test and antibiotic test using disc diffusion method. Antibiotic test was performed on oral bacteria and Staphylococcus aureus. The results obtained six fungal isolates from Apis dorsata Binghami's nest, namely isolates FAB1, FAB2, FAB3, FAB4, FAB5 and FAB6. The results of the antagonist test showed that the isolates FAB1, FAB2, FAB3, FAB4 and FAB5 were antagonistic. The results of the antibacterial test showed that all isolates produced an average bacterial growth inhibition of 17-18 mm on Staphylococcus aureus and isolates of oral bacteria. The inhibition zone lasts up to 3 x 24 hours so that the activity of the bacteria is bactericidal. From the results of this study, it can be concluded that the endogenous fungus Apis dorsata Binghami is a potential source of antibacterial bioactives.